Sexual dimorphism in Ceraeochrysa cubana (Neuroptera : Chrysopidae) - Penny, N. D.; de Freitas, S. (Kansas Entomological Soc, 2001)
Sexual dimorphism of green lacewings is discussed, citing previously known examples of this structural phenomenon on the frons, antennal scape, and forewings. Newly recognized dimorphism is cited in Ceraeochrysa cubana for the vertex and abdominal spiracles.